2009
DOI: 10.1007/s10479-009-0584-6
|View full text |Cite
|
Sign up to set email alerts
|

A characterization of chain probe graphs

Abstract: International audienceA chain probe graph is a graph that admits an independent set $S$ of vertices and a set $F$ of pairs of elements of $S$ such that $G+F$ is a chain graph (i.e., a $2K_2$-free bipartite graph). We show that chain probe graphs are exactly the bipartite graphs that do not contain as an induced subgraph a member of a family of six forbidden subgraphs, and deduce an $O(n^2)$ recognition algorithm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In fact, as pointed out in (Golumbic et al 2009), an O(n 2 )-algorithm can be derived from the proof of Theorem 1.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…In fact, as pointed out in (Golumbic et al 2009), an O(n 2 )-algorithm can be derived from the proof of Theorem 1.…”
mentioning
confidence: 89%
“…The second one characterizes these graphs via a certain "enhanced graph": G is a chain partitioned probe graph if and only if the enhanced graph G * is a chain graph. This is analogous to a result on interval (respectively, chordal, threshold, trivially perfect) partitioned probe graphs, and gives an O(m 2 )-time recognition algorithm for chain partitioned probe graphs.Given a graph class C, a graph G = (V , E) is called a C probe graph if there exists an independent set S ⊆ V and a set E ⊆ S 2 such that the graph G = (V , E ∪ E ) is in the class C, where S 2 stands for the set of all 2-element subsets of S. Probe graphs have been investigated for various graph classes; see Golumbic et al (2009) and the literature given there for more information.In case of bipartite graphs without induced 2K 2 (a graph with four vertices and two disjoint edges), also called chain graphs by Yannakakis (1981) or difference graphs by Hammer et al (1990), Golumbic et al (2009) very recently found a characterization of chain probe graphs as follows; notice that chain probe graphs are necessarily bipartite. Theorem 1 (Golumbic et al 2009) Let G be a bipartite graph.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A characterization of chain probe graphs and an O(n 2 ) recognition algorithm was given in Golumbic et al (2009). The partitioned chain probe graph problem assumes that the independent set S is given and fixed in advance, and is a special case of the chain sandwich problem where E 2 \ E 1 = S × S. The complexity of the partitioned chain probe problem has also been shown to be polynomial in Van Bang (2010).…”
Section: Graph Sandwich Problem For Propertymentioning
confidence: 99%
“…Chordal probe graphs were investigated in [11] and a characterization and recognition algorithm was given in [2] for both the partitioned and non-partitioned versions. Recently, characterizations and recognitions have been given for chain probe graphs in [12], and for threshold probe graphs and trivially-perfect probe graphs, also known as quasi-threshold probe graphs, in [4]. Other probe classes are to be found in [5,6].…”
Section: Introductionmentioning
confidence: 99%